Kearifan Lokal Sumba Timur Dalam Tradisi Cium Hiung (Papuduk) Sebagai Sumber Media Pembelajaran Sosiologi Di SMA Negeri 1 Nggaha Ori Angu - Faizah Ulumi Firdausi; Yanus Ndunu Tura Amah (Peneliti.net, 2023)
Sumba Island is an island located in East Nusa Tenggara Province which is known for its rich culture and traditions because many cultures are passed down from generation to generation from the legacy of their ancestors. The people of East Sumba are a society that is rich in culture, and has all kinds of traditions that are carried out from generation to generation, namely one of them,